Legal issues concerning the use of antibiotics in animal production - Lipińska, Izabela (Przegląd Prawa Rolnego, 2020)
The purpose of the considerations is to answer the question whether the legal regulations adopted at the EU and national level serve to protect animal health and allow for safe use of antibiotics in animal production. The authoress concludes that the legal standards currently in force unequivocally determine the admissibility of the use of antibiotics in enumerated situations, outside of which their use is prohibited and carries a risk of a specific sanction. However, these standards are not observed. Thus, they do not serve to protect animal health and only to a limited extent stimulate their safe use in production. It seems that the weakness of controls and an easy access to antibiotics are responsible for the low effectiveness of the legal regulations adopted both at the EU and national level.